Utilization of Interactive Multimedia to Improve the Understanding of Autistic Students - Dhiaulhaq, Shifiyan Ahmad; Arianto, Fajar (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to improve the cognitive abilities of 4–5-year-old children in Group A of TK Aisyiyah Bustanul Athfal Mamboro using number card media. A two-cycle Classroom Action Research (CAR) design (Kemmis & McTaggart) was employed (Rahman et al., 2017). Ten preschoolers (2024/2025 academic year) participated. Data were collected via classroom observations, interviews, and assignments, then analyzed descriptively by calculating percentage improvements. The results showed significant increases in cognitive performance from the pre-intervention stage to Cycle II. For example, the proportion of children correctly observing and naming numbers rose from 40.0% (pre-test) to 80.0% (Cycle II), and those recognizing number symbols improved from 36.7% to 80.0% (Cycle II). On average, cognitive skill indicators increased by about 40% between cycles. It can be conclude that using number card media effectively enhanced the children’s mental abilities.